Stress in the zoo: Tracking the impact of stress on memory formation over time. (September 2016) - Vogel, Susanne; Schwabe, Lars
Highlights: Stress is known to affect human memory formation, but precisely how remains unclear. We tracked stress effects on memory over more than 2 h to unravel the exact time course. Two different physiological stress response waves enhanced memory formation. Immediate stress effects on memory were linked to the autonomic nervous system. Slower enhancing effects of stress were associated with the cortisol stress response. Abstract: Although stress is well known to modulate human memory, precisely how memory formation is altered by a stressful encounter remains unclear. Stress effects on cognition are mainly mediated by the rapidly acting sympathetic nervous system, resulting in the release of catecholamines, and the slower acting hypothalamus-pituitary-adrenal axis secreting cortisol, which induces its effects on cognition through fast, non-genomic actions and delayed, genomic actions. Importantly, these different waves of the physiological stress response are thought to dynamically alter neural processing in brain regions important for memory such as the amygdala and the hippocampus. However, the precise time course of stress effects on memory formation is still unclear. To track the development of stress effects on memory over time, we tested individuals who underwent a stressful experience or a control procedure before a 2-h walk through a zoo, while an automatic camera continuously photographed the events they encoded. In a recognition memory test one week later, participants were presented with target photographs of their own zoo tour and lure photographs from an alternate tour. Stressed participants showed better memory for the experimental treatment than control participants, and this memory enhancement for the stressful encounter itself was directly linked to the sympathetic stress response. Moreover, stress enhanced memory for events encoded 41–65 min after stressor onset, which was associated with the cortisol stress response, most likely arising from non-genomic cortisol actions. However, memory for events encoded long after the stressor, when genomic cortisol actions had most likely developed, remained unchanged. Our findings provide novel insights into how stress effects on memory formation develop over time, depending on the activity of major physiological stress response systems.